Effectiveness of Reduced Radioiodine Activity for Thyroid Remnant Ablation after Total Thyroidectomy in Patients with Low to Intermediate Risk Differentiated Thyroid Carcinoma - Todica, Andrei; Haidvogl, Sabine; Fendler, Wolfgang Peter; Ilhan, Harun; Rominger, Axel; Haug, Alexander Robert; Bartenstein, Peter; Lehner, Sebastian (Nuklearmedizin - NuclearMedicine, 2017)
Aim: To compare the success rates of radioiodine therapy (RIT) for thyroid remnant ablation (TRA) after the administration of a high-standard activity (3700 MBq; 100 mCi) to a lower-activity regimen of 2000 MBq (54 mCi) I-131 in a cohort of differentiated thyroid carcinoma (DTC) patients (papillary, follicular, mixed, pT1a(m) – pT3, N0 – NX, R0). Methods: 135 patients received approx. 2000 MBq I-131 (54 mCi) for thyroid remnant ablation after total thyroidectomy for DTC, 137 patients received approx. 3700 MBq (100 mCi) I-131. Ablation success was defined as thyroglobulin (TG) levels < 0.5 ng/ml after stimulation, negative I-131 whole-body scan and inconspicuous results on neck ultrasonography approximately 6 months after initial RIT. Results: In the follow-up 84.4 % of patients in the reduced-activity group and 87.6 % of the patients in the standard-activity group did not show any relevant residual I-131 uptake in the thyroid bed (p = 0.454). 90 % in the reduced-activity group and 91 % in the standard-activity group demonstrated a stimulated TG level < 0.5 ng/ml (p = 0.969). All patients were unre-markable in cervical ultrasonography. The success rate was comparable in both groups (81.5 % in the reduced-activity group vs. 83.9 % in the standard-activity group, p = 0.592). No re-therapy was required in 85.2 % of the patients in the low-activity group as compared to 87.6 % of the patients in the standard-activity group (p = 0.563). Conclusions: We could demonstrate that irrespective of the activity administered, the patients had comparable success rates with regard to TRA as defined by our criteria. We thus consider the use of a reduced-activity regimen for TRA safe and feasible in the patient cohort examined in this study.
Keywords: Differentiated thyroid carcinoma; remnant ablation; radioiodine; reduced activity; outcome